The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1111/jog.12980
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of less radical treatment for patients with early invasive uterine cervical cancer

Abstract: Aim: Radical trachelectomy (RT) with lymphadenectomy has become a standard treatment modality for patients with early invasive uterine cervical cancer who hope to preserve fertility. However, pregnancy after RT has high risks of preterm birth. The possibility of more conservative RT and the application of RT for patients with higher clinical stages were studied. Methods: The medical charts and specimens of 42 patients who underwent RT and 64 patients who underwent radical hysterectomy were retrospectively stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…And our study revealed that a simple trachelectomy 20 mm not 10 mm below the internal os with pelvic lymphadenectomy might be possible for stage 1A2 patients [26]. These results might indicate the possibility of more conservative trachelectomy such as simple trachelectomy with a shorter amputation of the uterine cervix which lead to the improvement of the obstetrical prognosis for stage 1A2 patients [26,27].…”
Section: Discussionsupporting
confidence: 54%
“…And our study revealed that a simple trachelectomy 20 mm not 10 mm below the internal os with pelvic lymphadenectomy might be possible for stage 1A2 patients [26]. These results might indicate the possibility of more conservative trachelectomy such as simple trachelectomy with a shorter amputation of the uterine cervix which lead to the improvement of the obstetrical prognosis for stage 1A2 patients [26,27].…”
Section: Discussionsupporting
confidence: 54%
“…As we reported recently, more conservative vaginal RT might be possible in patients with stage 1B1 or less without affecting the oncological prognosis. Especially in patients with stage 1A2, simple trachelectomy might be possible …”
Section: Discussionmentioning
confidence: 99%
“…Especially in patients with stage 1A2, simple trachelectomy might be possible. 16 RT during pregnancy might still be an experimental treatment modality. In addition, obstetrical management after RT is also very difficult.…”
Section: Discussionmentioning
confidence: 99%
“…However, vaginal RT is a more conservative operation than abdominal RT. Vaginal RT resects the parametrium at the level of type II hysterectomy, whereas abdominal RT can provide wider resection up to the level of type III resection [22]. Does such a conservative procedure of vaginal RT affect the recurrence of the cancer?…”
Section: Discussionmentioning
confidence: 99%